Використання моделей лінійного передбачення для факторизації параметричних спектрів - Медінцев, Р. В. (ХНУРЕ, 2021)
To analyze complex composite processes, it is proposed to use a multiplicative autoregressive model. Expressions describing such a model are presented. Decomposition of a complex multimode parametric spectrum of the process into simple components is substantiated. The model can be used to solve a number of problems in statistical radio engineering and artificial intelligence.
Keywords: передбачення; параметричний спектр